Principals Managerial Leadership Strategy in Maintaining the Sustainability of New Student Enrollment - Wawan Kuswanda; R Supyan Sauri; Saeful Anwar (At Turots: Jurnal Pendidikan Islam, 2026)
The decline in the number of new students poses a significant challenge to the sustainability of secondary schools, especially in non-urban areas. This study aims to analyze the managerial leadership strategies of school principals in maintaining the sustainability of new student enrollment at SMAN 1 Cisaga, Ciamis Regency. Using a qualitative approach, data were collected through in-depth interviews, observations, and documentation with participants consisting of the principal, teachers, and parents. The results of the study show that there are three main strategies that are consistently implemented: strategic planning that involves collaboration with the community, implementation of adaptive and technology-based school promotion programs, and continuous evaluation of the effectiveness of the strategies implemented. The principal plays a key role in building a positive image of the school through the development of extracurricular programs, strengthening community relations, and optimizing digital communication media. These strategies have proven to strengthen the school's appeal and increase community trust in educational institutions. This study concludes that inclusive, participatory, and responsive managerial leadership to social dynamics is key to maintaining the stability of new student enrollment. Further studies are recommended to include more schools and external variables to broaden the relevance of this research.